Pre-operative factors for predicting a difficult laparoscopic cholecystectomy - Bhardwaj, Rajni; Bali, Rajandeep Singh; Zahoor, Yawar (International Surgery Journal, 2018)
Background: Laparoscopic cholecystectomy is a very safe procedure yet there are instances where serious complications can be avoided and better managed if the surgeon is forewarned or prepared in advance for them. So, a need is felt to identify pre-operative parameters for anticipating a difficult cholecystectomy. Methods: This study was carried over a period of two years (2007- 2009). Patients having symptomatic cholelithiasis willing to undergo laparoscopic cholecystectomy were enrolled in the study. The following pre-operative parameters were evaluated in the study: age, sex, body mass index, history of previous abdominal surgery, history of acute cholecystitis, history of biliary colic, palpable lump in right hypochondrium, experience of the surgeon and abdominal ultrasonogram (following parameters were noted increased gallbladder wall thickness, number of stones, size of largest stone and its location). Results: Acute cholecystitis, palpable gall bladder, increased gallbladder wall thickness, biliary colic, gall stones >2 cm in size, gall stone impacted at gallbladder neck and BMI >30 kg/m2 had a significant p-value in a difficult laparoscopic cholecystectomy. Conclusions: Further research is needed to formulate a score based on the variables mentioned above to predict a difficult laparoscopic cholecystectomy and hence letting the surgeon be better prepared for any eventualities that he encounters whilst performing laparoscopic cholecystectomy.